2016
DOI: 10.24275/uam/izt/dcbs/hidro/2016v26n3/oseguera
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macroinvertebrates of two tropical, high-mountain lakes at Nevado de Toluca Volcano at central region of Mexico

Abstract: 2016. Macroinvertebrados bentónicos de dos lagos tropicales de alta montaña en el volcán Nevado de Toluca, en la región central de México. Hidrobiológica 26 (3): 419-432. RESUMENAntecedentes. Los macroinvertebrados bentónicos son importantes debido a su papel en la remineralización de la materia orgánica y como indicadores por ser sensibles a las perturbaciones derivadas de las actividades humanas. Objetivos. Analizar la distribución espacial y temporal de la riqueza taxonómica y la densidad de los macroinvert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the lakes of Montebello, Chiapas, the families Chironomidae, Hyalellidae, Coenagrionidae and Scirtidae are recorded as the most dominant (Guadarrama-Hernández et al, 2015;Orozco-Martínez, 2016). The high mountain lakes, El Sol and La Luna del Nevado de Toluca (Oseguera et al, 2016), recognize only eight species of macroinvertebrates, mainly oligochaetes, chironomids and bivalves standing out for their abundance.…”
Section: Discussionmentioning
confidence: 99%
“…In the lakes of Montebello, Chiapas, the families Chironomidae, Hyalellidae, Coenagrionidae and Scirtidae are recorded as the most dominant (Guadarrama-Hernández et al, 2015;Orozco-Martínez, 2016). The high mountain lakes, El Sol and La Luna del Nevado de Toluca (Oseguera et al, 2016), recognize only eight species of macroinvertebrates, mainly oligochaetes, chironomids and bivalves standing out for their abundance.…”
Section: Discussionmentioning
confidence: 99%
“…For zooplankton biomass, we took the reported average biomass [ 35 ] and multiplied it by the zooplankton carbon percentage measured in this study. For benthic organisms, we used the reported biomass directly [ 47 ], except for gastropods, because this is the first study that sampled and reported gastropods ( Physa sp.) in El Sol; for those, we used an average biomass value to calculate a neutral hyperparameter α and to avoid further bias in their contribution to the rainbow trout diet.…”
Section: Methodsmentioning
confidence: 99%